برامج قناة الشروق تي في و الثقافة الصحية للمرأة الجزائرية - دراسة ميدانية على عينة من نساء ولاية جيجل - - زرزايحي, زوبير (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة إلى التعرف على دور برامج قناة الشروق تي في في نشر الثقافة الصحية لدى المرأة الجزائرية ولإجراء هذه الدراسة؛ تم الاعتماد على منهج المسح بالعينة؛ كون الدراسة تنتمي إلى الدراسات الوصفية، وعلى ضوء أهداف الدراسة ولجمع البيانات حول الموضوع تم الاستعانة باستمارة الاستبيان التي وزعت على عينة تتكون من مشاهدي البرامج التلفزيونية الصحية لقناة الشروق تيفي والتي قدرت بـثمانين مفردة من النساء بولاية جيجل؛ حيث تم تفريغ البيانات وتحليليها؛ وتوصلنا إلى نتائج مفادها أن أفراد العينة يتابعون البرامج الصحية من أجل التثقيف واكتساب المعلومة الجيدة ،وأيضا الاهتمام بهذه المواضيع من أجل الاستفادة من النصائح والإرشادات التي تقدمها والتي كان لها تأثير إيجابي ودور فعال في زيادة الثقافة الصحية لدى المرأة الجيجلية. Abstract: The study aimed to identify the role of Al-Shorouk TV programs in spreading health culture among Algerian women, and to conduct this study; The sample survey method was used; Since the study belongs to descriptive studies, and in light of the study’s objectives and to collect data on the subject, a questionnaire was used, which was distributed to a sample consisting of viewers of health television programs for Al-Shorouk TV, which was estimated at 80 women in Jijel; Where the data was unloaded and analysed; And we reached results that the sample members follow the health programs in order to educate and acquire good information, and also pay attention to these topics in order to benefit from the advice and instructions they provide, which had a positive impact and an effective role in increasing the health culture of the Jijelian women.
Al-Shorouk TV programs and the health culture of Algerian women - a field study on a sample of women in jijel
مقال
Keywords: المرأة الجزائرية ، الثقافة ، الثقافة الصحية ، البرامج الصحية ، البرامج; programs , television programs , culture , health culture , Algerian women